Cell phone testing and fundamental scientific research. - Lin, James C. (IEEE Antennas & propagation magazine.)
There is a lack of scientific consensus on experimental studies that provide clear evidence either refuting or supporting the cancer induction or promotion potential of RF and microwave radiation from cell phones. The uncertainties persist, in part, because of the limited number and scope of studies that have been undertaken. There is a concern that an established effect from wireless radiation, even small, could have a considerable impact in terms of public health. The author discusses these issues.